IMPLEMENTASI STRATEGI PEMBELAJARAN INKLUSIF BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Lastini, Fitri; Sri Haryanti; Minsih, Minsih; Choiriyah Widyasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to describe learning strategy inklusif for children with special needs in elementary school classes. This study employs a qualitative approach with field research methods. The research was conducted at SD Negeri 02 Wonokeling, Jatipuro, Karanganyar. The implementation of inclusive education at SD Negeri 02 Wonokeling shows significant efforts in accommodating the needs of special needs students through adaptive learning, the role of shadow teachers, and parental involvement. However, challenges such as teacher qualifications, curriculum adaptation, government support, and infrastructure still need to be addressed. Continuous professional development for teachers is crucial to enhance the effectiveness of inclusive education. This study underscores the importance of collaboration among schools, parents, and the government to achieve quality inclusive education for all students.